Analisis Kandungan Antiseptik Daun Kopasanda (Choromolaena odorata) sebagai Dasar Pembuatan Gel pada Luka - Maulinda Nurhajanah; Lalu Agussalim; Siti Zuhratul Iman; Titi Laily Hajiriah (Bioscientist : Jurnal Ilmiah Biologi, 2020)
Kopasanda (Chormolaena odorata) leaves are often used as traditional medicine and are proven to be used as natural antiseptics. We use this public belief as the basis for analyzing the antiseptic content in laboratory tests. The test results are then used as the basis for making the gel. The method we use is the maceration method to proceed to the phytochemical screening test. Based on the results of the analysis, it can be concluded that, it is true that Kopasanda leaves (Choromolaena odorata) contain antiseptic compounds that can heal wounds.